1991
DOI: 10.1002/jez.1402600108
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in plasma thyroxine binding in turtles

Abstract: The relation between seasonal changes in plasma thyroxine (T,) and T, binding activity was studied in three species of turtle previously shown to differ in the nature of their binding proteins; additional direct measurements of a high affinity T, binding protein (TBP) were made in one species using RIA. In the painted turtle, Chrysemyspicta (Family Emydidae), a species with large seasonal changes in plasma T,, the binding protein measured by activity and RIA showed significant seasonality. Binding activity cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The results of the present study showed that not all thyroid hormones were correlated with TP and albumin levels in regard to either sex or season. This is in contrast to the results of previous studies, 10‐13,20 in which the binding proteins (TBP and albumin) and tT4 levels were highly correlated. Licht et al 12 reported that TBP in turtles ( T scripta ) was near the albumin fraction on polyacrylamide‐gel electrophoresis, which correlated with the α1‐fraction in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study showed that not all thyroid hormones were correlated with TP and albumin levels in regard to either sex or season. This is in contrast to the results of previous studies, 10‐13,20 in which the binding proteins (TBP and albumin) and tT4 levels were highly correlated. Licht et al 12 reported that TBP in turtles ( T scripta ) was near the albumin fraction on polyacrylamide‐gel electrophoresis, which correlated with the α1‐fraction in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…It is known that only a small portion of the total circulating thyroxine is in the "active" or "free" form; the remainder is bound to highaffinity plasma proteins [22]. Further, the serum concentrations of these binding proteins appear to vary seasonally in some species [23,24], although this has not yet been examined in the ewe. Thus, the amount of thyroid hormone available for exerting action might change with season despite an unaltered total serum thyroxine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The highest T 4 levels were found during metabolic depression in the lizard Cnemidophorus sexilineatus (Sellers et al, 1982) and T 3 levels were highest during torpor in woodchucks (M. monax) (Young et al, 1979a). However, a large number of studies have found thyroid hormones decrease during or just prior to the hibernation period in a wide variety of animals, including black bears (Ursus americanus) (Azizi et al, 1979;Lundberg et al, 1976;Tomasi et al, 1998), the Finish brown bear (U. arctos arctos) (Hissa et al, 1994), hedgehogs (E. europaeus) (Fowler, 1988), iguanas (Dipsosaurus dorsalis) (John-Alder, 1984), painted turtles (Chrysemys picta) (Licht et al, 1991), thirteen-lined ground squirrels (S. tridecemlineatus) (Tomasi and Stribling, 1996) and echidnas (Tachyglossus aculeatus) (Nicol et al, 2000). Other studies have shown that levels of thyroid hormone reach their lowest levels during the hibernation period, but levels begin to increase towards the end of the hibernation period.…”
Section: T4mentioning
confidence: 99%